Proliferating cells nuclear antigen (PCNA) expression in normal tissues, benign and malignant (metastatic and not metastatic) differentiated human thyroid tumors - Guda, B. B.; Pushkarev, V. V.; Zhuravel, O. V.; Kovalenko, A. Ye.; Pushkarev, V. M.; Zurnadzhi, L. Yu.; Tarashchenko, Y. M.; Tronko, M. D. (Reports of the National Academy of Sciences of Ukraine, 2015)
PCNA expression in normal tissues, benign and malignant (metastatic and not metastatic) human thyroid tumors was studied. In malignant tumors and follicular adenoma tissue, the increased PCNA expression was observed, and the amount of antigen in tumor tissue, except for follicular carcinoma, exceeded the amount in the conditionally normal tissue. Importantly, in encapsulated papillary carcinomas tumors, this excess was 85%, while, in not encapsulated metastatic tumors, the PCNA amount was more than 3 times at the mean above normal and — in the most aggressive tumors with metastases in lungs — even 4 times. Thus, the PCNA amount in thyroid tissue can serve as a diagnostic and prognostic marker, and effective antigen inhibitors development may be a promising trend in thyroid cancer treatment.